The nutcracker - Tchaikovsky, Peter Ilich, 1840-1893.; Chase, Lucia, 1897-1986.; Smith, Oliver Lemuel, 1918-1994.; Baryshnikov, Mikhail, 1948-; Brandt, Yanna; Kirkland, Gelsey; Minz, Alexander; Young, Gayle; Wilson, Sallie; Conover, Warren; Osborne, Gregory; Wright, Rebecca, 1947-2006.; et al. (West Long Branch, NJ : Distributed by Kultur Video, West Long Branch, NJ : Distributed by Kultur Video, 2004)
The chief attraction of this 1977 adaptation is the pairing of Baryshnikov and Kirkland. In consequence, the storyline has been altered to keep Clara and the Nutcracker prince as the focus of the tale. At a Christmas party, Clara is presented with the elegant Nutcracker prince by her doting godfather, Herr Drosselmeyer. A drunken male guest breaks it, and Clara is devastated. That night, Clara dreams about the Nutcracker prince: he comes to life, fights off the Rat King and his minions, and takes her to his kingdom. There she is royally entertained, and they dance together. Shy and diffident Clara longs to remain in the dream world--safe on the brink of adulthood--but her love for her godfather and her family draw her back into the waking world, where adulthood and real romance await her.
Overture -- Introduction/Start of Act I -- March of the wooden soldiers -- 1st doll dance -- 2nd doll dance -- 3rd doll dance -- Nutcracker dance -- Mice & soldiers -- Snowflake's dance -- Overture/Start of Act II -- Spanish dance -- Chinese dance -- Court jester's dance -- Marzipan dance -- Russian dance -- Flower dance -- Sugar Plum Fairy dance -- Finale.
Originally produced for broadcast in the US by CBS on December 16, 1977.
Production designer, Boris Aronson ; costume designer, Frank Thompson ; director of photography, Larry Boelens ; conductor, Kenneth Schermerhorn ; choreography for "Snowflake" waltz by Vasily Vainonen ; videotape editors, Gary Princz, Max Curtis.
Mikhail Baryshnikov (Nutcracker/Prince), Gelsey Kirkland (Clara), Alexander Minz (Drosselmeyer), Gayle Young (Mr. Stahlbaum), Sallie Wilson (Mrs. Stahlbaum), Warren Conover (Fritz, Clara's brother), Gregory Osborne (Harlequin), Rebecca Wright (Doll), George De La Pena (Moor), Marcos Paredes (King of mice); featured soloists: Cynthia Harvey, Jolinda Menendez, Rodney Gustafson, Charles Maple, Eric Nesbitt, Clark Tippet, Hilda Morales, Kirk Peterson, Aurea Hammerli, Roman Jasinski, Nanette Glushak, Narie Johansson, Victor Barbee, Richard Schafer; narrator, Norman Rose.
MPAA rating: Not rated.
DVD; Region 0 (All), NTSC; 5.1 Dolby digital surround, 2.0 Dolby digital stereo; full screen presentation, aspect ratio 1.33:1.
Keywords: Ballets; Nutcrackers (Implements) -- Drama; Children's dreams -- Drama; Ballets -- Television adaptations; Christmas television programs; Children's television programs; Fantasy television programs; Cultural television programs; Television musicals; Television programs; Television programs -- United States; Fantasy -- Feature; Youth -- Feature